Duração do período pré-imaginal e fecundidade de Chrysoperla externa (Hagen, 1861) (Neuroptera: Chrysopidae) em diferentes populações e gerações - de Bortoli, Sergio Antonio [UNESP]; Ferreira, Raimundo José [UNESP]; Vacari, Alessandra Marieli [UNESP]; de Bortoli, Caroline Placidi [UNESP]; de Magalhães, Gustavo Oliveira [UNESP]; Dibelli, Wanderlei [UNESP] (My University, 2012)
The lacewings appear in many agroecosystems, preying several species of agricultural pests. They have great search capability, high voracity, high reproductive potential and are easily maintained in laboratory conditions. In laboratory rearing, to avoid problems in the mass production are recommended adjustments in the type and quality of prey to be used in order to obtain individuals with desirable characteristics. It is necessary special care with the laboratory populations, avoiding problems from inbreeding. Larvae were reared individually in Petri dishes (9.0 cm diameter) and fed with eggs of Sitotroga cerealella (Olivier, 1789) (Lepidoptera: Gelechiidae), in the amount of 25 mg / larva, while the adults were kept in PVC cylindrical cages (10 cm × 30 cm). Thus, the study analyzed the influence of the size of the population of Chrysoperla externa (Hagen, 1861) (Neuroptera: Chrysopidae) on the pre-imaginal period (egg to adult) and reproductive capacity of this specie come from different populations and generations of laboratory. To this end, we used two populations, one of Jaboticabal (F 8 and F 21) and one of Piracicaba (F 6 and F 15), and subpopulations of 1, 5, 10, 15 and 20 couples, analyzing the incubation of eggs and the number of eggs per female in each population, generation and subpopulation. The pre-imaginal period (egg to adult) and the number of eggs per female of C. externa are influenced by the generation and the number of founding individuals, being these parameters favored when laboratory populations are established with the largest number of couples.
Fecundity and pre-imaginal period of Chrysoperla externa (Hagen) (Neuroptera: Chrysopidae) under different populations and laboratory generations
Keywords: Biological aspects; Laboratory rearing; Lacewing; Oviposition capacity; Pre-imaginal period